Hesiod's cosmos - Clay, Jenny Strauss (Cambridge University Press, 2003)
In the Theogony and the Works and Days Hesiod provides the earliest systematic and comprehensive account of the genesis of the Greek gods and the nature of human life. Hesiod's Cosmos argues for reading the two poems as complementary halves of a whole embracing the divine and human cosmos.